Enhancing Brand Loyalty: From Sensorial Experience to Affective Experience - Nurul Izzah; Suwandi Sumartias; Susie Perbawasari (Ikatan Sarjana Komunikasi Indonesia, 2023)
This research discusses a café in Makassar city called Pyur For You café, which provides an exciting experience to its consumers. This research analyzes how brand loyalty can form through sensory experience and affective experience. This research is a qualitative case study with informants from Pyur For You café consumers selected randomly and met directly in the café area. This research involved three consumers who have come to the café repeatedly and recommended the café to their relatives. From the findings of this research, consumers of Pyur For You cafe have received a sensory experience in the cafe area through their sight, smell, taste, and hearing. After receiving a sensory experience, it successfully forms a compelling consumer experience. Sensory experience and affective experience then become variables that help to increase brand loyalty. However, its application can still be maximized again.